Evaluación del impacto ambiental de los pesticidas utilizados para el control de plagas en los principales cultivos hortícolas en el valle de Chancay-Huaral, Lima - Rodríguez-Quispe, Susana Patricia (2023)
An environmental impact assessment was carried out in the Chancay-Huaral valley for tomato, bell pepper, cucumber, carrot, and lettuce crops. Additional surveys and interviews were conducted to 96 farmers and 10 of the main pesticide supplies in the area. We determined that for the tomato crops between 33 to 42 pesticides applications were made with 27 active ingredients; for the bell pepper crops 36 to 45 applications with 28 active ingredients; for the cucumber crops 22 applications with 19 active ingredients; for the carrot crops 8 applications with 11 active ingredients; and for the lettuce crops 12 applications with 15 active ingredients. For these applications, the farmers prepared the mixtures using commercial formulations or according to their own criteria, guided by the suppliers. Due to the number of applications carried out, the pesticide withdrawal periods were not respected, and phytosanitary management was based mainly on chemical control without consideration of an Integrated Pest Management program. The environmental impact per hectare of pesticides per campaign for the crops studied was 541.30 for tomato, 595.97 for bell pepper, 959 for cucumber, 125.38 for carrot, and 81.88 for lettuce. This study will serve as a baseline for the assessment of environmental impacts of various agricultural crops, and to evaluate the implementation of Integrated Pest Management programs.